Fiscal Policy in an Islamic Framework: A Bibliometric Coupling Analysis (2016–2025) - kartini; Fadly (Ecopreneur : Jurnal Ekonomi dan Bisnis Islam, 2026)
The development of Islamic fiscal policy has become a strategic issue in the modern economy in line with increasing income distribution inequality, state fiscal pressures, and demands for sustainable development. Based on maqāṣid al-sharīʿah, Islamic fiscal policy offers a normative approach that emphasizes distributive justice, social welfare, and the role of the state through the instruments of zakat, infaq, alms, waqf, and ethical public spending. This research aims to map the intellectual structure, patterns of literary linkages, and the direction of research development at the intersection of Islamic fiscal and economic policy. The method used is a qualitative descriptive approach with a coupling bibliometric analysis of the publication for the period 2021–2025 sourced from the Dimensions database, then visualized using the VOSviewer software. The results show the formation of several interconnected main clusters, with specific documents and authors occupying a central position based on high total link strength, reflecting conceptual consolidation in the themes of fiscal justice, redistribution instruments, and the integration of modern fiscal policies with sharia principles. In conclusion, the Islamic fiscal policy literature shows a strong level of scientific integration and cohesion, and has the potential to be an important foundation in the development of fair, inclusive, and sustainable public policies.